Nursing students' experiences from clinical education using the TPSN model - Vahid Zamanzadeh; Leila Valizadeh; Akram Ghahramanian; Maryam Namadi-Vosoughi; Farzaneh Bagheriyeh; Afsaneh Pourmollamirza (BMC, 2024)
Abstract Background The TPSN model is an innovative model to create an integration and structured relationship between educational and healthcare provider institutions. This model is done to reduce the theoretical-practical gap in nursing. The present study aimed to explore the experiences of nursing students. Methods In a conventional content analysis, 11 undergraduate nursing students, 7 graduate nursing students, and 4 doctoral students were selected. Data was collected through focus group discussions and individual interviews. Results The findings from analyzing the students' experiences who had received education using this model resulted in four main categories: the feeling of being a nurse, an integrated and collaborative clinical education platform, the development of nursing clinical education, and educational challenges. Conclusion The TPSN model provides a suitable platform for nursing clinical education. This model helps students integrate theoretical knowledge with clinical practice and helps them act as professional nurses in the future.